'Inspiring Conversations': A Comparative Analysis of the Involvement of Experts by Experience in Italian and Scottish Social Work Education. (3rd December 2020) - Cabiati, Elena; Levy, Susan
Abstract: The involvement of service users and carers, Experts by Experience (EBE), in social work education at the Catholic University of Milan, Italy, and the University of Dundee, Scotland, is rooted and connected epistemologically and pedagogically. Differences emerge in how these roots are manifest in the models of EBE involvement adopted in the two universities. This article explores these similarities and differences through discussion of the different models of EBE involvement in use at the two European universities, and thus provides a comparative European insight into approaches, experiences and impact of EBE involvement in social work education. The authors contextualise the pedagogy and core values underpinning EBE involvement and introduce the concept of 'inspiring conversations'. The comparative analysis is centred on five areas of EBE involvement in social work education: context and types of involvement; recruitment of EBE; roles and responsibilities of EBE; resource implications; and impact and outcomes of involvement. The article calls for a focus on 'Coherence', 'Prudence' and 'Sustainability' as a foundation for other universities to enhance their social work programmes through cultivating EBE involvement to co-create knowledge to inform future innovative practice.